Advancing preoperative assessment of the motor system through navigated transcranial magnetic stimulation-based mapping of the supplementary motor area in patients with glioma - Schwendner, Maximilian; Zhang, Haosu; Kram, Leonie; Krieg, Sandro; Ille, Sebastian (Neurosurgical focus, 2025)
OBJECTIVE Resection of gliomas within the superior frontal gyrus can result in prolonged and, in some cases, persistent supplementary motor area (SMA) syndrome. This highlights the need to accurately identify the cortical SMA and its underlying fiber tracts. In this study, the authors utilized navigated transcranial magnetic stimulation (nTMS) mapping and function-based fiber tractography to delineate the SMA in patients with frontal brain tumors. METHODS Continuous theta burst stimulation was performed over six stimulation targets in the pre-SMA and SMA proper within the superior frontal gyrus. Patients performed the nine-hole peg test during stimulation using the hand contralateral to the stimulation. RESULTS The study included 22 patients with a mean age of 47.7 ± 17.3 (range 25.3-79.4) years without motor deficits (11 low-grade gliomas, 11 high-grade gliomas), 12 (54.5%) of whom had left-sided lesions. Navigated TMS-positive sites were observed equally on both hemispheres (right: median 3 [range 2-4] vs left: median 3 [range 1-4], p = 0.694). Six patients (27.3%) developed a prolonged SMA syndrome postoperatively, persisting at the 3-month follow-up examination. Additionally, 1 patient (4.5%) exhibited permanent motor deficits related to the primary motor area. In patients with prolonged SMA syndrome, the number of resected nTMS-positive SMA sites was significantly higher, with a median of 2 (range 2-3) compared with 0 (range 0-2) in patients without SMA syndrome (p = 0.004). Resection of nTMS-positive SMA points showed a sensitivity of 100% and a specificity of 73.3% for the occurrence of a prolonged SMA syndrome. On the subcortical level, resection of the frontal aslant tract (FAT) showed the highest specificity (0.867) and negative predictive value (0.929). Combining findings of the FAT and frontostriatal tract resulted in a specificity of 0.667, with a sensitivity and negative predictive value of 1.00. CONCLUSIONS Navigated TMS-based mapping of the SMA is feasible, accurate, and reliable. Resection of nTMS-positive cortical sites and underlying subcortical fiber tracts provides excellent sensitivity and negative predictive value for the occurrence of prolonged SMA syndrome. However, these data are currently insufficient to fully elucidate the occurrence of SMA syndrome. Navigated TMS-based mapping of the SMA should be performed in addition to nTMS motor mapping in motor eloquent brain lesions to identify at-risk patients and optimize surgical outcomes.
Gesehen am 08.12.2025